COMPARING THE STRUCTURES OF INDONESIAN CHILDREN’S WRITINGS IN THE NARRATIVE OF HAPPY VS. SAD EXPERIENCES - Kushartanti, Bernadette; Johanna, Raina Dellani; Dewi, Fitria Rahma (Masyarakat Linguistik Indonesia, 2024)
This study investigated Indonesian school-age children’s written narratives of their experiences involving happy and sad emotions. A question addressed in this study is: do different themes influence the composition of the components in the narratives? This study aimed to explain the children’s ability to produce narratives in written forms by focusing on the structures and comparing the components of the narratives on two experiences, applying Labov & Waletzky’s (1997) narrative components. The participants were elementary school students, aged 8–11 years (N = 131). All the children were assigned two writing tasks: one on a happy and one on a sad experience. Differences in themes in narratives were examined quantitatively. We identified the components of the narratives and classified them into complete, incomplete, complex, singular, and plural narratives. It was found that the children could already write cohesive stories, but some skipped certain components of the narratives. Differences between the stories were found in the number of clauses and the components.